Performance Analysis of the Parit Baru Bengkayang Coal Fired Power Plant Project (2 X 50 Mw) in Terms of Cost and Schedule Using the Earned Value Method - Simanungkalit, Robertus; Adi, Tri Wahyu (Syntax Literate, 2026)
This study aims to evaluate the performance of the construction project of the Parit Baru Site Bengkayang Steam Power Plant (2 x 50 MW) in terms of cost and time using the Earned Value Management (EVM) method. Common issues in large-scale construction projects include delays and cost overruns, which negatively affect the efficiency and effectiveness of project implementation. EVM is an analytical method that integrates the measurement of time and cost performance, allowing the assessment of deviations from the initial project plan.This research uses actual project cost and schedule data obtained from monthly PLTU progress reports. Analysis was conducted on key variables such as Planned Value (PV), Earned Value (EV), and Actual Cost (AC). By calculating performance indicators such as the Cost Performance Index (CPI) and Schedule Performance Index (SPI), it was revealed that the project experienced deviations in both schedule and cost. The results of the analysis show that EVM provides comprehensive information on project performance and is highly beneficial as a control tool for future projects. This study also provides recommendations to improve the effectiveness of planning and control in similar electricity infrastructure projects.